(untitled) (International Journal of Health, Animal Science and Food Safety, 2015)
Interest in mycoplasmas stems from their importance as serious animal and human pathogens, their frequent contamination of cell lines and, because of their small size, for their use as models of the minimal cell concept. They have traditionally been seen as highly host specific but this is being reviewed in view of recent detections of animal mycoplasmas in unlikely hosts including humans. Some highlights include: • Mycoplasmas, containing as few as 450 genes, are the smallest free-living organisms on the planet • They were the first synthetically created life forms • While the majority of mycoplasmas are harmless, the World Organisation for Animal Health (OIE) have listed 4 mycoplasma diseases because of their serious socio-economic impacts • 10-15% of cell lines used for virus research are contaminated with mycoplasma Are they the real the causes of TSEs and other undiagnosed human conditions?